(untitled) (Bangladesh Journal of Pharmacology, 2016)
This study was aimed to explore the pharmacological basis of potential medicinal use of Elaeagnus umbellata in gut disorders. Crude extract of E. umbellata, which was found positive for flavonoids, terpenoids and tannins, provided 9.9-71.9% protection in castor oil-induced diarrhea in mice, like verapamil. In isolated rabbit jejunum preparations, crude extract caused inhibition of spontaneous and high K+-induced contractions, with respective EC50 values of 0.3 (0.1-0.5) and 0.5 mg/mL, suggesting Ca2+ channel blockade (CCB). Pretreatment of tissue with crude extract (0.11 mg/mL) caused a rightward shift in Ca2+ concentration-response curves. With the exception of aqueous fraction, n-hexane, chloroform and ethyl acetate inhibited spontaneous and high K+-induced contractions and displaced rightward Ca2+ concentration-response curves. Extract was found safe up to 10 mg/kg in mice. Our data shows that anti-diarrheal effect of crude extract of E. umbellate is due to CCB-mediated spasmolytic effect, concentrated in the ethyl acetate fraction and suggests its medicinal importance in diarrhea and spasm. Video Clip of Methodology: Isolation of rat jejunum: 2 min 32 sec Click to watch